Pengembangan Perangkat Pembelajaran Model Discovery Learning Berbasis Standar Kompetensi Kerja Nasional Indonesia (SKKNI) - Trisna Muliawan; Pince Salempa; Sugiarti Sugiarti (Program Pasca Sarjana UNM, 2021)
This is a development research that aims to evolve a learning instruments discovery learning model based on the SKKNI on volumetric analysis subject that are valid, practical, and effective. The development model used in this study refers to the 4D, which consists of the defining, design, development, and dissemination. The learning instruments developed are RPP, LKPD, Student Learning Materials, and THB. The SKKNI-based discovery learning model volumetric learning device that was developed was then validated by two experts. After validation, a learning device trial is then conducted at the SMK-SMAK Makassar in class XI E with a total of 35 students. The results of the study indicate that the SKKNI-based discovery learning model developed after being validated was very accurate (V = 3.75). The learning device is stated to be practical because the practicality test related to: (1) the implementation of the learning device is in the fully implemented category (M = 1.86) included in the category (1.5 ≤ M ≤ 2.0), (2) the teacher gave a very positive response with a percentage of 93.49%, and (3) the students gave a very positive response with a percentage of 91.93%. This learning device also meets the effectiveness criteria, which are reviewed through learning outcomes with a classical percentage of completeness 94.00%. Therefore, the results of the study indicate that the developed learning device products meet valid, practical, and effective criteria.